Effect of real estate investment on economic growth in Kisii county, Kenya - Ombongi, Catherine Gesare; Nyakundi, Wallace Atambo; Mogwambo, Vitalis A. (ijssit.com, 2016)
Real Estate Investment Trust is an investment vehicle for real estate that is comparable to a mutual fund, allowing both small and large investors to acquire ownership in real estate ventures, own and in some cases operate commercial properties such as apartment complexes, hospitals, office buildings, timberland, warehouse, hotels and shopping malls. This study focuses on whether; real estate investment trust in residential, commercial and industrial sector has any effect on economic growth of Kisii County, Kenya. The study found out that the majority of the property owned by real estate developers in Kisii County is for residential use, the majority of the respondents have been in business between 3-5 years, many real estate investors started their business with the help of personal savings, he majority enter into real estate business because of the rise in property investment, there is no investor who used less than Kshs. 20,000 as the startup capital, thus implying that many real estate investors used more than Ksh 80,000 as initial capital to invest, most real estate investments are owned by owners, there has been growth immensely since the investor started the business and that is why so many have ventured into the business, increase in lease charges has led to increase in real estate business, the increase in clientele has motivated many to venture into real estate in Kisii County and it also found out that the real estate investment in Kisii County is in demand hence there is growth.
Keywords: Economic Growth; Real Estate Investment